160k views
3 votes
HELP PLZZZZZ !!!!!!!! I DON'T UNDERSTAND

HELP PLZZZZZ !!!!!!!! I DON'T UNDERSTAND-example-1
User Alswl
by
5.0k points

1 Answer

6 votes

Answer:

C.

Explanation:

As seen below, the equation of a circle is (x - h)^2 + (y - k)2 = r^2.

In this case, h = the x-value of the center of the circle, which is -2, and k = the y-value of the center of the circle, which is 3. The radius r is 4.

(x - (-2))^2 + (y - (3))^2 = (4)^2

(x + 2)^2 + (y - 3)^2 = 16

This corresponds to answer choice C.

Hope this helps!

HELP PLZZZZZ !!!!!!!! I DON'T UNDERSTAND-example-1
User ColinTea
by
4.6k points